1998
DOI: 10.1097/00005537-199803000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic Pretreatment With Betamethasone on the Bacterial Flora, Inflammatory Response, and Polyp Formation in Experimentally Infected Rabbit Maxillary Sinus Mucosa

Abstract: To investigate possible effects of corticosteroids on polyp formation and local bacterial colonization, pneumococcal sinusitis was experimentally induced in rabbits pretreated with betamethasone or saline. After 7 days, macroscopic polyps were counted post-mortem and on histologic slides after serial sectioning. Histologic sections were also examined with light microscopy. Macroscopic polyps were significantly fewer in animals given betamethasone, while there was no difference regarding the number of microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The authors felt that the steroids offered a mucosal protective effect in sinus wound healing. 12 Our study provides additional insight into the use of corticosteroids, specifically in sinusitis therapy. Using the currently accepted animal model for sinusitis, the rabbit, we were consistently able to introduce pseudomonal sinus infections.…”
Section: Discussionmentioning
confidence: 85%
“…The authors felt that the steroids offered a mucosal protective effect in sinus wound healing. 12 Our study provides additional insight into the use of corticosteroids, specifically in sinusitis therapy. Using the currently accepted animal model for sinusitis, the rabbit, we were consistently able to introduce pseudomonal sinus infections.…”
Section: Discussionmentioning
confidence: 85%
“…We propose that the main reasons for this [21][22][23] are: (1) as an intranasal corticosteroid, budesonide mainly had a focal biological effect on rhinosinus mucosa with lower systemic bioavailability and had no influence on the hypothalamic-pituitary-adrenal axis function; (2) small doses of corticosteroid did not affect the phagocytosis of macrophages. Norlander et al [23] reported about the effect of systemic pretreatment with betamethasone on the bacterial flora, inflammatory response, and polyp formation in experimentally infected rabbit maxillary sinus mucosa, which showed that the amount of macroscopic polyps in animal sinus mucosa decreased significantly in the betamethasone group, and Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…15 In another study, systemic pretreatment with betamethasone in experimentally infected rabbit maxillary sinus mucosa reduced inflammatory response, polyp formation, and pathogenic strains. 16 The use of fluticasone dipropionate aqueous nasal spray for the postoperative control of recurrent nasal polyps seemed to be associated with a higher incidence of acute pansinusitis than beclomethasone dipropionate spray. 17 There are only a few studies of the effect of topical nasal steroids on MCC.…”
Section: Discussionmentioning
confidence: 99%